REPORT ON THE 2ND MEETING OF THE EXPERT COUNCIL, PERTAINING TO THE ISSUES OF THE EXTERNAL TREATMENT FOR ATOPIC DERMATITIS - article editorial (Union of pediatricians of Russia, 2007)
(Педиатрическая фармакология. - 2007;4(6):79-80).